“It is difficult to be absolutely sure one way or the other.” – a mixed method study on Finnish physicians’ views on euthanasia and physician-assisted suicide - Reetta P. Piili; Minna Hökkä; Elina Tolvanen; Jukka Vänskä; Pekka Louhiala; Juho T. Lehto (BMC Medical Ethics)
Abstract Background Euthanasia and physician-assisted suicide (PAS) are complex and ethically challenging topics. Physicians’ attitudes toward euthanasia and PAS have been studied, but little is known about their ethical considerations regarding these topics. This study aimed to assess Finnish physicians’ views on assisted dying (AD), including euthanasia and PAS. Our special emphasis was to describe physicians’ views on the legalization of AD, their views on AD as a phenomenon, and how AD reflects on physicians’ roles. Methods A survey including statements and open questions concerning euthanasia and PAS was sent to all Finnish physicians in 2020. The data was analysed using quantitative measures and a qualitative approach. Results Altogether, 6889 physicians answered the survey, yielding a response rate of 26%. Of the responders, 9% fully agreed that accepting euthanasia would benefit the physician-patient relationship, while 19% fully agreed that it would harm this relationship. From 2565 responders, 3033 answers were received to the open questions. The qualitative analysis yielded two unifying categories, firstly ‘Physicians’ views on assisted dying (AD) in the current societal situation and on its legalization’ included three main categories namely: ‘AD and end-of-life issues in the current societal situation’ (f = 230), ‘Physicians perspectives on legalisation of AD’ (f = 605) and ‘The possible consequences of legalizing AD’ (f = 543). Secondly, the unifying category ‘Physicians views on AD as part of their work and as a phenomenon’ included two main categories, ‘AD and the physicians’ professional role (f = 650) and ‘AD as a multifaceted phenomenon’ (f = 296). Conclusion Assisted dying is seen as a complex issue, and it was difficult to form an opinion on it. Physicians and the care team are faced with ethical dilemmas about topics related to AD, even though it is not legalized in Finland. Open and pluralistic discussion on AD, including ethical aspects, implications for society and end-of-life care practices is of utmost importance.